Publisher's Note: Observation of the baryonic B decay B[bar]0 → Λ+cΛ[bar]K- [Phys. Rev. D 84, 071102(R) (2011)] - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
We report the observation of the baryonic B decay ¯¯¯B0→Λ+c¯¯¯ΛK− with a significance larger than 7 standard deviations based on 471×106 B¯¯¯B pairs collected with the BABAR detector at the PEP-II storage ring at SLAC. We measure the branching fraction for the decay ¯¯¯B0→Λ+c¯¯¯ΛK− to be (3.8±0.8stat±0.2sys±1.0Λ+c)×10−5. The uncertainties are statistical, systematic, and due to the uncertainty in the Λ+c branching fraction. We find that the Λ+cK− invariant-mass distribution shows an enhancement above 3.5 GeV/c2.